Sustainability and Indigenous People: The Inuit Case - Jelinčič, Klemen (Slovene Anthropological Society / Društvo antropologov Slovenije, 2003)
In this paper I shall try to examine the connection between the concept of sustainable development and indigenous peoples, such as the Inuit. As one of the best solutions to the growing environmental crisis, the idea of sustainable development has gained prominence in recent years, including in the international arena. Also, in recent years the ways and knowledge of indigenous peoples have been included in possible solutions to such a crisis as indigenous populations are certainly one of the few human communities that have lived sustainably on the territories, which they have occupied for centuries. I shall try to elaborate this connection in general and particularly with the example of the Inuit, an indigenous people residing in the Arctic. The Inuit have shown that sustainability of an area is clearly connected to the political autonomy of the communities concerned. Furthermore, the ideologies lying at the base of their self-construction as a community, as it may be seen through subsistence practices, are clearly related to the concept of sustainability and may even be categorized as such. Specific focus shall be given to the Yup'ik community with an attempt to picture the subsistence cycle of its members, to the Inupiaq whaling activities as an example of a particular sustainable subsistence activity within an extensive cultural and political context, and to the Inuit Circumpolar Conference, the most important Inuit NGO that promotes indigenous political autonomy and sustainable management in the circumpolar areas. Članek predstavlja poskus identifikacije povezave med trajnostnim konceptom in staroselskimi ljudstvi, v tem primeru Inuiti. Kot eden najboljših pristopov do rešitve naraščajoče ekološke krize, je trajnostni princip v zadnjih letih tudi v mednarodni areni pridobil na veljavi. Istočasno so v zadnjih letih znanja in vednosti staroselskih ljudstev začela z vključevanjem v reševanje tovrstne krize, saj so staroselske skupnosti vsekakor ene redkih človeskih skupnosti, ki so na svojih področjih ...